2022
DOI: 10.1155/2022/2124710
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Perception Research of Artificial Intelligence in Environmental Public Health Physiotherapy Nursing for the Elderly

Abstract: This perceptual study focuses on developing artificial intelligence for elderly care design. It analyses and discusses the role of artificial intelligence in elderly care and its application to physiotherapy care. Artificial intelligence, as an emerging disruptive technology, is releasing the enormous energy accumulated in the technological and industrial revolutions, profoundly transforming how humans produce, live, and think about the world. Economic development and social progress are significantly impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Similar analogies can most surely be applied to mitigating or averting multiple aging states and adverse health conditions or disabilities, and health providers are strongly encouraged to gain a comprehensive understanding of the AI potential in advancing health across the lifespan and its strengths and limitations. 4 The potential for AI to foster optimally safe and enriching living environments may further enable improvements in self-care activities, mobility, recreational opportunities, social interactions and internet mediated community-based health promotion programs to many. Public health workers may find AI highly advantageous for promoting mass communications and needs based resource allocations that can reduce age associated health disparities in diverse ways, as well as time and monetary costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar analogies can most surely be applied to mitigating or averting multiple aging states and adverse health conditions or disabilities, and health providers are strongly encouraged to gain a comprehensive understanding of the AI potential in advancing health across the lifespan and its strengths and limitations. 4 The potential for AI to foster optimally safe and enriching living environments may further enable improvements in self-care activities, mobility, recreational opportunities, social interactions and internet mediated community-based health promotion programs to many. Public health workers may find AI highly advantageous for promoting mass communications and needs based resource allocations that can reduce age associated health disparities in diverse ways, as well as time and monetary costs.…”
Section: Discussionmentioning
confidence: 99%
“…Excluded were articles that did not focus specifically on this set of issues, and those that were non English based articles. For a comprehensive overview, the article by Shi et al, 4 is recommended.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%